Phase 1 First‐in‐Human, Single‐ and Multiple‐Ascending Dose, and Food Effect Studies to Assess the Safety, Tolerability, and Pharmacokinetics of Presatovir for the Treatment of Respiratory Syncytial Virus Infection. (17th April 2018) - German, Polina; Xin, Yan; Chien, Jason W.; Weng, Winnie; Mackman, Richard; Lewis, Sandra A.; Meng, Amy; Ling, John; Mathias, Anita
Abstract: Respiratory syncytial virus (RSV)‐associated respiratory tract infection is a leading cause of hospitalizations in infants for which no effective treatment exists. RSV infection is also an important cause of respiratory disease in adults and immunocompromised patients. Presatovir (GS‐5806) is an orally bioavailable antiviral agent that inhibits fusion of RSV with host cell membranes. Here, results from 2 phase 1 studies that evaluated safety, tolerability, and pharmacokinetics of presatovir in healthy adults following administration of single and multiple (7 days) once‐ or twice‐daily ascending doses (first‐in‐human study) and in the presence or absence of food (food effect study) are described. Presatovir exhibited favorable safety and pharmacokinetic profiles that supported once‐daily dosing. Presatovir exposure increased in an approximately dose‐proportional manner across the evaluated dose range (single doses 25‐300 mg; multiple doses 10‐75 mg once daily for 7 days). Administration of presatovir with a high‐fat meal did not alter exposure, supporting administration without regard to a meal in further clinical studies. These data were subsequently used to inform presatovir dosing regimens in a phase 2a challenge study of adults experimentally infected with RSV. Collectively, results from phase 1 evaluations and a phase 2a challenge study support further clinical investigation of presatovir for the treatment of RSV infection.